Civil Dispute Resolution Strategy Through Alternative Dispute Resolution (ADR) - Marlinda Martha Fenny Pandi; Sri Astutik; Fitri Ayuningtiyas; Vivi Sylvia Purborini (Civiliza Publishing, 2026)
Civil dispute resolution in Indonesia is generally conducted through litigation; however, court proceedings are often time-consuming, costly, and tend to produce win-lose outcomes that may harm the relationship between the disputing parties. As an alternative, Alternative Dispute Resolution (ADR) offers a more efficient and constructive approach to resolving civil disputes. This study aims to examine the background of ADR as a strategy for civil dispute resolution and to analyze the effectiveness of mediation in court proceedings. This research employs a normative legal method using statutory and conceptual approaches. Primary legal materials include Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and Supreme Court Regulation (PERMA) Number 1 of 2016 on Mediation Procedures in Courts. Secondary materials such as legal literature and scholarly journals support the analysis. The data are analyzed descriptively and qualitatively. The findings indicate that ADR is philosophically grounded in the values of Pancasila, particularly deliberation and consensus, and sociologically aligned with Indonesia’s customary tradition of peaceful settlement. Although mediation is mandatory in civil cases, its effectiveness remains limited due to a lack of good faith from disputing parties, insufficient public understanding, and suboptimal implementation. In conclusion, ADR, particularly mediation, serves as a relevant and strategic mechanism for resolving civil disputes in Indonesia, but its success depends on the parties’ willingness to settle and the effective role of mediators and courts.